2011
DOI: 10.1007/s10529-011-0764-8
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression and activity of human DNA polymerase iota in loach embryos

Abstract: Human DNA polymerase iota (Pol ι) is a Y-family DNA polymerase with unusual biochemical properties and not fully understood functions. Pol ι preferentially incorporates dGTP opposite template thymine. This property can be used to monitor Pol ι activity in the presence of other DNA polymerases, e.g. in cell extracts of tissues and tumors. We have now confirmed the specificity and sensitivity of the method of Pol ι activity detection in cell extracts using an animal model of loach Misgurnus fossilis embryos tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…We have previously demonstrated that the misincorporation activity of Pol ι in intact loach could not be detected at any stage of development [ 21 ]. After injection of human Pol ι encoding gene into loach embryos, we have observed the appearance of activity of this enzyme in cellular extracts of GFP-expressing larvae ( Figure 1 B) by using the radiolabeled primer extension method [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that the misincorporation activity of Pol ι in intact loach could not be detected at any stage of development [ 21 ]. After injection of human Pol ι encoding gene into loach embryos, we have observed the appearance of activity of this enzyme in cellular extracts of GFP-expressing larvae ( Figure 1 B) by using the radiolabeled primer extension method [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA fragments corresponding to human Pol ι cDNA along with 60 bp 5’-untranslated region sequence were inserted between the NcoI and BamHI sites of pEGFP-C1 vector (Clontech, Montain View, CA, USA), downstream of a cytomegalovirus (CMV) promoter, to generate the fusion protein eGFP-POLI (pEGFP-POLI vector), as described previously [ 21 ]. The plasmid containing cDNA encoding an inactive mutant form of the Pol ι protein (D126A-E127A) fused with eGFP was generated using site-specific mutagenesis of pEGFP-POLI vector by Evrogen (Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation